Social Media and Supply Chain - Sonja Markova; Tatjana Petkovska-Mirčevska (Amfiteatru Economic)
Web 2.0, also referred to as social media, is the use of the World Wide Web to increase creativity, information sharing, and collaboration among users. Social media is driving the rethinking of many of the principles of economics. The use of social media within supply chains is lagging behind their usage for other operational functions, however supply chain management is evolving into supply chain management 2.0.The purpose of this article is to provide researches of the supply chain management a reference with the main concepts of social media: social profiles, social applications, brand outposts and communities, and the social ecosystem.